Providing acute care - Wijdicks, Eelco F. M., 1954- (Core principles of acute neurology., 2014)
The medical state of acutely hospitalized neurologic patients is often compromised. This title in Core Principles of Acute Neurology does focus on how certain neurologic conditions can inflict damage to other organ systems and what systemic complications most frequently jeopardize patients with primary neurological disorders. Providing Acute Care carefully summarizes the necessary orders and treatment plan and initial management of expected complications. Each system is discussed in a separate chapter and the crucial initial decisions are presented in an easy to read narrative.